Hazardous waste management practices in Malaysia: Current status, regulatory framework, and future directions - Mohammad Adam, Adman; Noridayu, Mah Hashim; Norazwina, Zainol; Nor Hazwani, Aziz (Hamadan University of Medical Sciences, 2025)
Poor hazardous waste management (HWM) poses a significant impact on the environment and human health. Although Malaysia has established policies and regulations governing the framework and outlining future directions for sustainable WM, implementing and monitoring the regulations are complex and rigorous. The need for continuous enhancement and renewal of regulations arises to keep pace with evolving technologies and changing circumstances associated with HW production. Therefore, this review critically examines HWM in Malaysia by synthesizing current regulations, relevant literature, and case studies, with an emphasis on recent technological and strategic developments. This study also delves into the current state of HWM practices in Malaysia, scrutinizing the existing regulatory framework and outlining future directions for sustainable WM. Moreover, this review aims to explore potential innovations and technologies that can shape the future landscape of HWM in Malaysia, thus ensuring a harmonious coexistence between industrial progress and environmental stewardship. Eventually, this work will provide a holistic overview of Malaysia’s HW landscape and offer forward-looking recommendations for strengthening environmental resilience, governance, and sustainability.